An autopsy case of asthmatic death: Usefulness of biochemical examination - Kinoshita Hiroshi; Kubota Akira; Kasuda Shogo; Nishiguchi Minori; Ouchi Harumi; Minami Takako; Matsui Kiyoshi; Yamamura Takehiko; Motomura Hiroyuki; Ohtsu Nao; Yoshida Shie; Adachi Nobuyuki; et al. (Vojnosanitetski Pregled)
Background. Asthma is the one of the major causes of sudden death in Japan. Postmortem diagnosis of asthma has been based on morphological findings in lungs, but it histological evidence, was also reported that the biochemical markers such as total and specific immunoglobulin E (IgE) are useful. Case report. We present here a case of fatal asthmatic death. A Japanese male in his thirties, complaining of dyspnea, collapsed suddenly. He was taken by ambulance to hospital, but cardiopulmonary resuscitation was ineffective. From autopsy findings, we concluded that the cause of death was asphyxia due to asthma attack. Biochemical findings indicated that the deceased had a severe asthmatic condition. Conclusion. In the presented case, the biochemical examination of the serum obtained at autopsy gave helpful information for the diagnosis that asthmatic attack was a cause of death.